2020
DOI: 10.2147/jpr.s250391
|View full text |Cite
|
Sign up to set email alerts
|

<p>Antinociceptive Effect of the Citrus Flavonoid Eriocitrinon Postoperative Pain Conditions</p>

Abstract: Background: Postoperative pain remains a major clinical problem as there are limited analgesic strategies that have been proven to be effective in preventing and relieving this type of pain. Natural products, including flavonoids, have distinct pharmacological properties and play an important role in the discovery of analgesic drugs. Materials and Methods: In this study, the flavonoid eriocitrin (eriodictyol 7-O-rutinoside), which is the main flavonoid in lemon fruit (Citrus limon), was mechanistically investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Taken together, the negative side effects associated with neuropathic and postoperative pain treatment reinforce the recommendations of evidence-based alternative therapeutics to treat these aforementioned pain conditions. Natural products, including herbals, flavonoids, and polyphenols, remain one of the most promising treatments for neuropathic [ 11 , 12 , 13 , 14 , 15 , 16 ] and postoperative pain [ 17 , 18 ]. Curcumin, also known as diferuloylmethane, is a polyphenolic compound present in the rhizomes of Curcuma longa (syn.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, the negative side effects associated with neuropathic and postoperative pain treatment reinforce the recommendations of evidence-based alternative therapeutics to treat these aforementioned pain conditions. Natural products, including herbals, flavonoids, and polyphenols, remain one of the most promising treatments for neuropathic [ 11 , 12 , 13 , 14 , 15 , 16 ] and postoperative pain [ 17 , 18 ]. Curcumin, also known as diferuloylmethane, is a polyphenolic compound present in the rhizomes of Curcuma longa (syn.…”
Section: Introductionmentioning
confidence: 99%
“…Some glycosidic forms of flavanones have also been described as potential GABAergic agents. For example, the anticonvulsant activity of hesperidin, hesperetin 7- O -rutinoside ( Table 3 ), could mediated by the modulation of GABA-BZD receptor [ 111 ], and the antinociceptive effects demonstrated in postoperative pain conditions by eriocitrin (eriodictyol 7- O -rutinoside, Table 3 ) could be mediated through opioid and GABA A Rs [ 114 ].…”
Section: Natural Products As Potential Gaba Modulatorsmentioning
confidence: 99%
“…It was indicated that aromatherapy with lavender and citrus aurantium relieved pain in conscious patients in an intensive care unit [ 13 ]. The antinociceptive effect of lemon aromatherapy was shown in mouse postoperative pain [ 14 ]. In another study, the antioxidant and antinociceptive effects of lemon citrus in mice were reported [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, CIH may relieve postoperative pain and subsequently improve physiological parameters, rehabilitation, and initial mobility, reducing the need for analgesics. Previous studies on the effect of inhaled lemon aromatherapy in patients with fractures are limited [ 14 ]; therefore, to improve the evidence-based practice, the present study aimed to determine the effect of lemon inhalation aromatherapy on pain, nausea, and vomiting as well as neurovascular assessment in patients for lower extremity fracture surgery.…”
Section: Introductionmentioning
confidence: 99%